Why is the IMF at an Impasse, and What Can Be Done about It?. Issue 3 (20th August 2015) - Wade, Robert H.; Vestergaard, Jakob
Abstract The International Monetary Fund is at an impasse, acutely short of secure lending resources. The main reason is that the US Congress is blocking ratification of an agreement reached in 2010 by all member states that would almost double its permanent loanable funds (its quota). World leaders should be worried that the Fund is currently relying on the good will of countries to supply it with short‐term loans which it can on‐lend to countries in crisis. This is not a solid foundation for the nearest thing the world system has to an international lender‐of‐last‐ resort. Since the IMF's multilateral functions cannot be readily replicated, it is important to find a way out. All solutions lead back to the US veto, the US being the only state (Treasury or Congress) able to veto supermajority decisions. The prospect of more financial crises ahead while the Fund is chronically short of secure lending resources should focus all minds on how to end the US veto. Otherwise the Fund will follow the WTO towards irrelevance, to the benefit of the few countries at the strong end of bilateral and regional arrangements.